The Effect of Ratio of Aloe Vera with Sweet Corn and Carboxy Methyl Cellulose Concentration on Quality of Aloe Vera Jam - Liston Preddy Pasaribu; Terip Karo-Karo; Sentosa Ginting (Universitas Sumatera Utara, 2015)
This research was conducted to determine the effect of ratio of aloe vera with sweet corn and Carboxy Methyl Celulose concentration on quality of aloe vera jam. This research was using a completely factorial randomized design with two factors: ratio of aloe vera with sweet corn (P): 90%:10%, 80%:20%, 70%:30%, 60%:40%, and CMC concentration (K): 0.5%, 1.0%, 1.5%, 2.0%. Parameters observed the water content, fiber content, protein content, total acid, total soluble solid, vitamin C content, spreadness value organoleptic color, aroma, and taste. The results showed that the ratio of aloe vera with sweet corn had highly significant effect on water content, fiber content, protein content, total soluble solid, color, aroma, and taste, and had no different effect on the total acid, vitamin C content and spreadness value. CMC concentration had highly significant effect on water content, fiber content, protein content, total soluble solid, and spreadness value, and had no different effect on the total acid, vitamin C, color, aroma, and taste. Interaction between ratio of aloe vera with sweet corn and CMC concentration had no different effect on all parameters. The ratio of aloe vera with sweet corn of 60%: 40% and 1.0% CMC concentration produced the best aloe vera jam. Keywords: Aloe vera, sweet corn, CMC, jam